The Model of the Formation and Implementation of the Creative and Innovative Potential of the Russian System of Higher Education - Gorbunov, Aleksandr Pavlovich; Gorbunova, Natalya Nikolaevna; Efimova, Ekaterina Vladimirovna; Kilinkarova, Sofiya Georgievna (International Journal of Economics and Financial Issues, 2016)
Theoretical interpretation and applied projection of the dynamics of the innovative role of higher education as a scientific basis for developing a model of the formation and implementation of the creative and innovative potential of the Russian higher education system are one of the most controversial problems of the modern Russian and world economy. The research is based on the principles of the system, system-situational and integrative approaches, macroeconomic and microeconomic analysis, methods of the structural and functional characteristics of the processes under study, research and projection of economic relations in their real dynamics with respect to their historical and logical origin. The integrating potential of the model of the transformative (creative and innovative) university is an adequate response to the challenges of the new era. This model allows to integrate and overcome a whole range of social and economic gaps in the public system precisely because it embodied the fundamental bases that meet the essence of the new era. Keywords: Russian higher education, knowledge economy, competency-based economy JEL Classifications: A20, A29, O53